Right atrial strain in Anderson–Fabry disease - Lillo, Rosa; Cianci, Alessio; Meucci, Maria Chiara; Iannaccone, Giulia; Di Brango, Claudio; Tusa, Filippo; Marsilia, Mario; Lanza, Gaetano Antonio; Lombardo, Antonella; Burzotta, Francesco; Graziani, Francesca (Frontiers in Cardiovascular Medicine, 2025)
BackgroundTo date, only limited data are available on right atrium (RA) morphofunctional remodeling in Fabry disease (FD).PurposeWe aimed to investigate RA structural and functional remodeling in patients with FD vs. healthy controls using 2D speckle tracking echocardiography (STE) and to explore whether any differences exist in FD patients with and without left ventricular hypertrophy (LVH).MethodsWe prospectively enrolled patients with FD and controls matched for age, sex, and cardiovascular risk factors. Patients with FD were divided in two groups according to the presence/absence of LVH (LVH+: left ventricular wall thickness >12 mm). All patients underwent standard echocardiography and STE analysis investigating the mechanics of all cardiac chambers, including RA reservoir, contractile and conduit strain.ResultsA total of 64 patients with FD (50% males; mean age 50 ± 17 years; 51.5% LVH+) and 64 control patients were included in the study. Focusing on right chambers, RA and right ventricular (RV) dimensions were similar between FD and controls. No differences were found for tricuspid annular plane systolic excursion (p = 0.073) and RV fractional area change (p = 0.461), while RV systolic Tissue Doppler velocity was reduced in patients with FD (p = 0.041). STE analysis revealed impaired strain values for all cardiac chambers in FD vs controls, specifically: left ventricular global longitudinal strain (LV-GLS, p < 0.001), left atrial (LA) reservoir strain (p = 0.001), conduit strain (p = 0.012), and contractile strain (p < 0.001), RV-GLS and RV free wall strain (p < 0.001). Similarly, all RA strain phases were significantly reduced in patients with FD compared with control patients (RA reservoir 27.4 ± 11.1 vs. 41.9 ± 8.3%, p < 0.001; RA contractile 9.9 ± 5.1 vs. 18.0 ± 4.9%, p < 0.001; RA conduit 19.1 ± 8.1 vs. 24.1 ± 8.1%, p = 0.001). When comparing FD patients without LVH to controls, it was found that RA reservoir and contractile strains were significantly reduced in the former (p < 0.001). In multivariable linear regression analyses, LA reservoir strain (p = 0.010) and LV-GLS (p = 0.044) emerged as independent correlates of RA mechanics after adjustments were made for RA dimensions, RV systolic function parameters and hypertrophy, and LV maximal wall thickness.ConclusionsIn FD impaired RA strain is a common finding. RA reservoir and contractile strains are reduced in FD patients even before LVH ensues, as compared to controls. LA reservoir strain and LV-GLS show an independent correlation with RA reservoir strain.